STRUKTUR LEGITIMASI DALAM MASYARAKAT INDONESIA (Studi Pengukuhan Kembali Kerajaan Gunung Sahilan Kabupaten Kampar Provinsi Riau) - Mulianto, Budi; Fikri, Rijalul (UIR PRESS, 2018)
Democratization in Indonesia provides an opportunity for the community to maintain and preserve the values, norms and beliefs of ancestors that are manifested in the cultural traditions and customs. Then to strengthen the tradition makes the existence of traditional institutions as a form of legitimacy and community identity. The existence of the Gunung Sahilan Kingdom that has experienced a leadership vacuum for a long time, raises questions, approximating what then makes Raja Gunung Sahilan re-established in the Gunung Sahilan Kingdom, traditional authority can be clearly seen from the royal structure that can be said to be not elite centric. The Kingdom of Mount Sahilan adopted a system of functional assignment within its government. The kingdom in the Kingdom of Gunung Sahilan as a symbol and symbol of the greatness of the institution. In the structure of the Kingdom of Gunung Sahilan Raja itself as the highest government that controls custom (government) and worship. Sahilan is